Upregulation of NETO2 expression correlates with tumor progression and poor prognosis in colorectal carcinoma. Issue 1 (December 2015) - Hu, Liang; Chen, Hai-Yang; Cai, Jian; Yang, Guang-Zhen; Feng, Dan; Zhai, Yan-Xia; Gong, Hui; Qi, Chen-Ye; Zhang, Yu; Fu, Hao; Cai, Qing-Ping; Gao, Chun-Fang
Abstract Background Neuropilin and tolloid-like 2 (NETO2) has been found to be overexpressed in different human cancers, but its expression pattern and clinical relevance in colorectal carcinoma (CRC) remains unknown. Methods Real-time quantitative PCR, western blot and immunohistochemistry analyses were used to analyze the expression of NETO2 in CRC clinical samples. The correlation of NETO2 expression with clinicopathologic features was estimated in a cohort containing 292 patients with primary CRC. Kaplan-Meier and Cox proportional hazards regression analyses were used to assess the prognostic value of NETO2 expression in CRC. Results The expression of NETO2 was frequently upregulated in CRC clinical samples at both the mRNA and protein levels, and its upregulation was significantly correlated with poor tumor differentiation (p = 0.013), advanced local invasion (p = 0.049), increased lymph node metastasis (p = 0.009), advanced TNM stage (p = 0.041) and increased patient death (p = 0.001). Kaplan-Meier analysis of the complete study cohort revealed that patients with high-NETO2 tumors had a significantly shorter disease-specific survival (DSS) than those with low-NETO2 tumors (p < 0.001). Importantly, high levels of NETO2 protein predicted poor DSS for patients with early stage tumors (p = 0.027) and for those with advanced stage tumors (p = 0.020). Furthermore, multivariate analyses indicated that increased NETO2 expression was an independent unfavorable prognostic factor for patients with early stage tumors (hazard ratio [HR] = 1.937, 95 % CI = 1.107-3.390, p = 0.021) as well as patients with advanced stage tumors (HR = 2.241, 95 % CI = 1.245-4.035, p = 0.007). Conclusions Our findings suggest that NETO2 upregulation could serve as a potential biomarker for the prediction of advanced tumor progression and unfavorable prognosis in patients with CRC.